Financial performance and working capital management practices in the retail sector: Empirical evidence from South Africa - Garikai Mandipa; Athenia Bongani Sibindi (Risks, 2022)
This study examines the relationship between the financial performance and working capital management practices of South African retail firms listed on the Johannesburg Stock Exchange. The study sample comprised a panel of 16 South African retail firms for the period 2010-2019. A fixed-effects estimator was employed in the analysis. The working capital management was proxied by average age of inventory (AAI), average collection period (ACP), average payment period (APP), and cash conversion cycle (CCC), while the financial performance was proxied by net operating profit margin (NOPM), return on assets (ROA), and return on equity (ROE). The key findings of the study documented the following: (1) There is a negative relationship between average collection period and financial performance. (2) A negative relationship between average age of inventory and financial performance measures (NOPM and ROA) was found. (3) The average payment period was found to be negatively related to return on equity. (4) The cash conversion cycle and net operating profit margin variables were found to be negatively related. The study concludes that working capital management practices influenced the financial performance of the South African retail firms. It is recommended that South African retail firms observe prudent optimal working capital management practices, as these influence their financial performance.
Keywords: 330; financial performance; financial sustainability; retail sector; South Africa; working capital management